SIFAT-SIFAT RUANG HASIL KALI DALAM-n KOMPLEKS - Sri Maryani (JURNAL ISTEK, 2011)
Inner product is an important concept to learn the properties of geometry in the plane or space. Its can be generalized to n-inner product spaces. This paper will reprove the properties of n-inner product spaces.